2019
DOI: 10.1111/pin.12798
|View full text |Cite
|
Sign up to set email alerts
|

CD109: a multifunctional GPI‐anchored protein with key roles in tumor progression and physiological homeostasis

Abstract: CD109 is a glycosylphosphatidylinositol‐anchored glycoprotein and a member of the α2‐macroglobulin/C3,C4,C5 family of thioester‐containing proteins first identified as being expressed on blood cells, including activated T cells and platelets, and a subset of CD34 + bone marrow cells containing megakaryocyte progenitors. Although CD109 carries the biallelic platelet‐specific alloantigen Gov, the physiological functions or roles of CD109 in human disease remain largely unknown. It was recently demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Although we found a novel upregulatory function of CD109 on TGF‐β signaling, one potential limitation of our study is that we could not elucidate the relationship between this upregulating effect of CD109 on TGF‐β signaling in tumor stroma and the downregulating effect of CD109 on epithelial cells, which was previously reported 12,14,23,48,49 . At present, the mechanisms underlying the paradoxical and context‐dependent effects of TGF‐β are still unclear 13,22 …”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although we found a novel upregulatory function of CD109 on TGF‐β signaling, one potential limitation of our study is that we could not elucidate the relationship between this upregulating effect of CD109 on TGF‐β signaling in tumor stroma and the downregulating effect of CD109 on epithelial cells, which was previously reported 12,14,23,48,49 . At present, the mechanisms underlying the paradoxical and context‐dependent effects of TGF‐β are still unclear 13,22 …”
Section: Discussionmentioning
confidence: 66%
“…We, however, observed that STAT3 phosphorylation was enhanced in CD109‐deficient cells in the previous study 23 . These controversial results suggested that STAT3 phosphorylation was regulated by CD109 in a complicated manner depending on the cell and tissue contexts 22 . CD109 also played a role in EGF signaling in glioma cells, 32 which was often activated by mutant EGFR in lung adenocarcinoma 37 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Cluster of differentiation 109 (CD109) is a glycosylphosphatidylinositol (GPI)‐anchored protein which belongs to the α2‐macroglobulin/C3, C4, and C5 family. CD109 was found to be expressed by endothelial, platelet, and hematopoietic progenitor cells 5 . The physiological function of CD109 in normal cells remains unclear, but it was reported that CD109 is upregulated in a wide variety of malignancies including squamous cell carcinomas, 6 glioblastomas, 7 melanomas, 8 and breast carcinomas 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these membrane proteins (tetraspanins, integrins and other surface proteins) on the EV surface could explain their increased uptake by recipient cells, as shown by the uptake assay (Figure 3), but also their potential to alter the behavior of recipient cells via activation of signaling pathways. Among these proteins, CD109 is a glycosylphosphatidylinositol-anchored glycoprotein acting as a multifunctional receptor associated with aberrant cancer cell proliferation 49 , integrin subunit beta 1 (ITGB1) and integrin subunit alpha V (ITGAV) both bind CX3C chemokine, attracting leukocytes as well as guiding EVs towards distinct target tissues 50,51 , transferrin receptor (TFRC) is a membrane glycoprotein that facilitates the cellular uptake 52 , sortilin 1 (SORT1) is involved in exosome release and transfer 53 , insulin like growth factor 2 receptor (IGF2R) is a tumor suppressor and a positive regulator of T-cell coactivation, facilitating immune cell responses and tumor invasion 24 . Another identified protein, was the specific melanoma glycoprotein non-metastatic b (GPNMB) which is a prometastatic and immunosuppressive molecule, previously reported to be present on melanoma exosomes 54,55 .…”
Section: Discussionmentioning
confidence: 99%